EFEKTIVITAS DAN EFESIENSI PENGELOLAAN KEUANGAN BADAN USAHA MILIK GAMPONG (BUMG) DALAM MENDUKUNG KEMAJUAN EKONOMI DESA - Nur, Muhammad; Halimah, Halimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
National economic progress will only be achieved if there is a good economic climate at the provincial level. Economic progress at the provincial level will be achieved if the district has good economic activity. The economic progress of a district can be achieved because of the contribution of a strong rural economy which has an impact on the welfare of the wider community. This will ensure good governance is implemented at all levels of development and decisions are based on the real needs of the people. Economic development in rural areas has long been carried out by the government through various programs. One of the programs to improve the rural economy is through the establishment of Village-Owned Enterprises (BUMDes) in Aceh. Villages are more closely named as Gampong. BUMG was born as a new approach in efforts to improve the village economy based on its needs and potential. BUMG management is fully carried out by the Gampong community. The way BUMG works is by accommodating community economic activities in an institutional form or business entity that is managed professionally but still relies on the original potential of the Gampong. This can make community businesses more productive and effective. This study aims to determine the Effectiveness and Efficiency of BUMG Financial Management in Glumpang Tiga District, Pidie District, with samples taken in 3 (three) Gampongs, namely Gampong Meunjee, Gampong Panjoe, Gampong Krueng Nyong. This study uses primary data from original data sources, the data analysis method used in this research is descriptive qualitative by managing the data obtained, to see BUMG’s financial management in Glumpang Tiga District, so it can be concluded that the effectiveness and efficiency of financial management Bumdes in Glumpang Tiga District, Pidie Regency, is running effectively or not. This is in accordance with the mandate of the village law so that it is able to make Gampong an independent villageKeywords : Analysis, Development, Banking